An Approach to Generalized Extending Modules Via Ec-Closed Submodules - Kamil, Enas Mustafa; Al-Aeashi, Shukur (Iraqi Journal of Science, 2023)
In this article, we introduce a class of modules that is analogous of generalized extending modules. First  we define a module M to be a generalized ECS if and only if for each ec-closed submodule A of M, there exists a direct summand D of M such that  is singular, and then we locate generalized ECS between the other extending generalizations. After that we present some of characterizations of generalized ECS condition. Finally, we show that the direct sum of a generalized ECS need not be generalized ECS and deal with decompositions for be generalized ECS concept.